(untitled) (مجلة إحالات, 2026)
This article presents an in-depth analysis of the cinematic adaptation of Naguib Mahfouz’s novel "The Beggar" (Al-Shahhat), directed by Houssam Eddine Mostafa in 1973. The study examines the artistic challenges of translating a philosophically introspective literary work into film, highlighting the narrative and thematic transformations from novel to screen. It explores how existential and nihilistic themes evolve in the adaptation process, with the film introducing explicit sociopolitical dimensions absent from the original novel. The article also focuses on the symbolic representation of female characters and their role in reflecting the tension between tradition and modernity in Egyptian society. Ultimately, the film is shown to offer a visually compelling interpretation of the protagonist’s existential crisis, mirroring the complexities of identity and the search for meaning in post-revolutionary Egypt.